Examining the cognitive flexibility of e-Sports players - Karakuş, Ozan; Yorulmazlar, Mehmet Mustafa; Çetin, Arif; Özsoy, Damla (VIREF Revista de Educación Física, 2024)
Objective: to investigate the cognitive flexibility of individuals involved in e-sports, with a focus on socio-demographic factors. Method: the Turkish version of the Cognitive Flexibility Inventory, as adapted by Sapmaz & Doğan (2013), was administered to a sample of 206 e-sports athletes who were selected via convenience sampling. The data were subjected to analysis using SPSS version 29.0.1.0 (171). The data obtained was analyzed using the Mann Whitney-U and Kruskal-Wallis tests. Results: based on the findings of the analysis, it was observed that within the cognitive flexibility inventory’s control sub-dimension, there was no significant difference in relation to the gender variable among e-sports participants aged 18-23. However, when considering the frequency of exercise variable, favorable outcomes were obtained for e-Sports participants who engage in regular exercise. Furthermore, based on the analysis of the frequency and variability of technological device usage during exercise, it was determined that there is a positive correlation between the frequency of utilizing technological devices and cognitive flexibility scores. Conclusion: consequently, the study’s findings indicate that female participants within the age range of 18-23, individuals who engage in regular exercise, and those who utilize technology devices during exercise exhibit elevated levels of cognitive flexibility. The investigation of cognitive flexibility among e-sports players has the potential to enhance their individual performance and elevate the overall professionalism of the e-Sports industry. Recommendations: to create and execute psycho-educational initiatives targeted at e-sports participants who exhibit limited cognitive flexibility. Competitive games are played under intense stress and pressure, which can adversely affect performance. These programs can help players develop stress coping strategies, enabling them to remain calmer and more focused during challenging moments and these programs aim to enhance the cognitive flexibility of e-sports participants, thereby improving their performance in competitive games, enabling them to effectively manage stress, and promoting a state of improved mental well-being. In this context, these programs can assist players in feeling better about themselves and becoming psychologically stronger. Enhancing mental well-being can help players approach games with a more positive attitude and play effectively for longer periods. Keywords: E-sports, Technology and Sport, Cognitive Flexibility.